Enhancing Compost Quality through Black Soldier Fly Larvae Bioconversion of Young Coconut Coir and Low-Carbon Organic Wastes - Dini Mufriah; T. Sabrina; Lisdayani Lisdayani (Agro Bali : Agricultural Journal, 2026)
Young coconut coir is an abundant high-carbon residue in Medan, North Sumatra, Indonesia, but its direct use as an organic amendment is limited by its fibrous structure and high C/N ratio. This study aimed to evaluate whether mixing young coconut coir with several low-carbon residues could improve the quality of frass produced by black soldier fly larvae. The experiment was arranged in a randomized complete block design with seven substrate treatments and three replications. The treatments consisted of young coconut coir alone and its mixtures with cauliflower leaf waste, pineapple skin waste, chicken manure, quail manure, goat manure, and cow manure. After 14 days of larval treatment, the frass was analyzed for moisture content, pH, total organic carbon, total nitrogen, C/N ratio, total phosphorus, and total potassium. The substrate mixtures significantly affected moisture content, pH, total organic carbon, total nitrogen, C/N ratio, and total potassium (P<0.01), but did not significantly affect temperature and total phosphorus. The mixture with quail manure produced the most favorable frass, characterized by low moisture content (30.84%), the highest total nitrogen (4.15%), the lowest C/N ratio (12.22), and the highest total potassium (4.59%). It also increased total nitrogen by 116.52% and total potassium by 51.38% compared with the initial substrate. These findings demonstrate that combining young coconut coir with nutrient-rich animal manure, particularly quail manure, is an effective strategy for producing nutrient-enriched BSFL frass suitable for use as an organic amendment.